Heritage yang Terlupakan Analisis Tantangan Museum Warisan Budaya di Era Museum Interaktif dan Digital - Hasanah, Enny Lisdayanti; Annisa Nur Majdina; Liza Enzelluthfiyah (Nazharat: Jurnal Kebudayaan, 2025)
The value of museums as cultural heritage has shifted from being merely cultural heritage to interactive and digital models due to rapid advances in digital technology. However, one of the many cultural heritage museums managed by the West Java Provincial Tourism and Culture Office, the Sri Baduga Museum located in the city of Bandung, is struggling to keep up with the digital trend. The purpose of this study is to analyze the challenges faced by the Sri Baduga Museum in preserving cultural heritage in the modern era. Additionally, it aims to identify strategies that can be implemented to enhance the museum's appeal while maintaining its cultural values. This research employs a qualitative approach, utilizing data collection methods such as interviews, field observations, and literature reviews related to museum digitization. The results of the study show that the problems that need to be addressed include budget constraints, lack of human and technological resources, and lack of supporting infrastructure. On the other hand, opportunities to use simple technologies such as QR codes, virtual tours, and social media can help market the museum. Collaboration between the government, academics, and cultural communities that drive museums remains important in preserving museums as cultural heritage.